HUBUNGAN ANTARA INDEKS LUAS DAUN DENGAN IKLIM MIKRO DAN INDEKS KENYAMANAN - Siti Badriyah Rushayati (Media Konservasi, 2012)
Air temperature and temperature humidity index in the urban was recorded as being higher compared to the surrounding area, while on the contrary the humidity is lower.  Lower air temperature, increased air humidity and reduced temperature humidity index could be achieved through the development of green open space area which considered aesthetical aspect and used plants with high leaf area index.  Statistical analysis showed that the increasing Leaf Area Index had caused the decrease of air temperature and the increase of humidity.  These conditions reduced the value of Temperature Humidity Index and increased human comfort. Keywords:   temperature,   humidity, Leaf Area Index, Temperature Humidity Index, green open space.